The potential of historical ecology to aid understanding of human–ocean interactions throughout the Anthropocene. Issue 2 (9th February 2022) - Thurstan, Ruth H.
Abstract: Marine historical ecology emerged in the scholarly literature with the aim of understanding long‐term dynamics in marine ecosystems and the outcomes of past human–ocean interactions. The use of historical sources, which differ in temporal scale and resolution to most scientific monitoring data, present both opportunities and challenges for informing our understanding of past marine ecosystems and the ways in which human communities made use of them. With an emphasis upon marine social‐ecological changes over the past 200 years, I present an overview of the relevant historical ecology literature and summarise how this approach generates a richer understanding of human–ocean interactions and the legacies associated with human‐induced ecosystem change. Marine historical ecology methodologies continue to be developed, whereas expanded inter‐ and multidisciplinary collaborations provide exciting avenues for future discoveries. Beyond scholarship, historical ecology presents opportunities to foster a more sustainable relationship with oceans going forward: by challenging ingrained perceptions of what is "normal" within marine ecosystems, reconnecting human communities to the oceans and providing cautionary lessons and exemplars of sustainable human–ocean interactions from the past. To leverage these opportunities, scholars must work alongside practitioners, managers and policy makers to foster mutual understanding, explore new opportunities to communicate historical findings and address the challenges of integrating historical data into modern‐day frameworks.